Espiración lenta total a glotis abierta como tratamiento fisioterapéutico en niños con bronquitis aguda. - Ilbay Saca, Irma Eliana (2023)
The project entitled Open Glottic Total Slow Breathing Out (ELTGOL) as a physiotherapeutic treatment in children with acute bronchitis aims to determine the efficacy of this technique in improving respiratory function in children with this pathology. It is a retrospective literature review with a mixed approach. It rigorously compiles and analyzes information from multiple studies on the physiological effects and benefits of ELTGOL in treating acute bronchitis in children. A literature search was conducted in PEDro, Dialnet, Elsevier, Google Scholar, LILACS, Medigraphic, PubMed, Redalyc, ResearchGate, SciELO, Science Direct, Scopus, and Scispace. The sample consisted of 25 articles that met the inclusion criteria, which were evaluated with the PEDro scale. The results of this review indicate that ELTGOL improves the quality of life of children with acute bronchitis since there is a reduction in bronchial obstruction due to a greater elimination of secretions. It is concluded that ELTGOL is a technique that, when correctly applied, is an excellent complementary alternative to the conventional treatment of pediatric acute bronchitis since it reduces the duration of hospitalization and the recurrence of the disease.